2019
DOI: 10.1029/2019ja026967
|View full text |Cite
|
Sign up to set email alerts
|

The Midlatitude Thermospheric Dynamics From an Interhemispheric Perspective

Abstract: Using Fabry‐Perot interferometers at five midlatitude stations (Boulder, Palmer, Millstone Hill, Mount John, and Kelan) in both hemispheres, we examine the interhemispheric and seasonal variations of midlatitude thermospheric dynamics. We also use the National Center for Atmospheric Research Thermosphere Ionosphere Electrodynamics General Circulation Model (TIEGCM) to simulate the seasonal changes of winds and the effects from Sub‐Auroral Polarization Streams. The observations and TIEGCM simulations show a cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…In addition, TIEGCM‐SAPS has been used to investigate the dynamics of the I–T system. Based on previous studies, a large degree of similarity between simulations and observations made with ground‐ and space‐based equipment has been achieved (e.g., Wang et al., 2012; Wu et al., 2019; Zhang et al., 2021). In summary, TIEGCM‐SAPS and TIEGCM‐default are reliable and can be applied to study the effects of SAPS on the equatorial ionosphere.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…In addition, TIEGCM‐SAPS has been used to investigate the dynamics of the I–T system. Based on previous studies, a large degree of similarity between simulations and observations made with ground‐ and space‐based equipment has been achieved (e.g., Wang et al., 2012; Wu et al., 2019; Zhang et al., 2021). In summary, TIEGCM‐SAPS and TIEGCM‐default are reliable and can be applied to study the effects of SAPS on the equatorial ionosphere.…”
Section: Resultsmentioning
confidence: 91%
“…TIEGCM is a three‐dimensional time‐dependent model of the coupled I–T system, which was developed at the High Altitude Observatory at the National Center for Atmospheric Research (NCAR/HAO). The TIEGCM is driven by the high‐latitude electric field based on the Heelis or Weimer models (Heelis et al., 1982), F 10.7 index that parameterizes the solar extreme ultraviolet and ultraviolet spectral fluxes (Richards et al., 1994), migrating and non‐migrating diurnal and semi‐diurnal tides from the lower atmosphere from the Global Scale Wave Model (GSWM; Hagan & Forbes, 2002, 2003), or tides derived from the Sounding of the Atmosphere using Broadband Emission Radiometry (SABER) and TIDI observations (Wu et al., 2019; Zhang et al., 2018). The horizontal resolution of the TIEGCM is 2.5° in GLat and 2.5° in Glon.…”
Section: Data and Modelmentioning
confidence: 99%
“…However, data‐model discrepancy is acceptable in model work due to a high degree of similarity in the temporal variations of SAPS velocity (Figures 2b–2c). TIEGCM has been used to explore the effects of SAPS on the global I−T system, and a good agreement between model outputs and observations has been achieved in previous studies (Wang et al., 2012, 2019; Zhang, Wang, et al., 2021). Both the large‐scale patterns of modeled and observed SAPS velocities were inversely proportional to those of Kp index (Figure 1b).…”
Section: Resultsmentioning
confidence: 60%
“…The real geomagnetic activity changes more rapidly with time, potentially causing differences between model predictions and satellite observations. Nevertheless, previous studies have reported that there is a large degree of similarity between simulations and observations from ground‐ and space‐based equipments (e.g., W. B. Wang et al., 2012; Wu et al., 2019).…”
Section: Discussionmentioning
confidence: 94%
“…Nevertheless, previous studies have reported that there is a large degree of similarity between simulations and observations from ground-and space-based equipments (e.g., W. B. Wang et al, 2012;Wu et al, 2019).…”
Section: Discussionmentioning
confidence: 95%